Tea tales: An analytical exploration of branding strategies and consumer trends in the tea industry - G. Surya; P. Anbarasan (Journal of Agriculture and Food Research)
Tea is the second most consumed beverage worldwide, with India playing a pivotal role in its production and trade. The Nilgiris district, one of India’s key tea-producing regions, contributes significantly to the industry through its cultivation of Orthodox and CTC teas. This study examines consumer preferences, branding strategies, and purchasing behavior concerning Brand A in the Nilgiris. It explores brand awareness, influential purchase factors, and promotional effectiveness using statistical techniques such as factor analysis and Rank-Based Quotient (RBQ). Findings indicate that taste, price, and aroma are primary consumer considerations, while free tasting, television advertising, and discount sales are the most effective promotional strategies. Notably, 63 % of respondents prefer Brand A due to its timely availability and perceived quality. The study also highlights challenges, including limited marketing efforts and the need for better brand positioning. While traditional retail outlets dominate tea purchases, digital marketing and strategic advertising could enhance Brand A’s reach. To maintain competitiveness, the brand must prioritize consumer engagement through improved promotions, optimized pricing, and expanded distribution. By leveraging effective advertising channels and consumer-centric marketing strategies, Brand A can strengthen its presence in the Nilgiris tea market.